Meaning Making in a Retirement Migrant Community: Religion, Spirituality, and Social Practices of Daily Lives - Spännäri, Jenni; Laceulle, Hanne (Frontiers in Psychology, 2021)
Meaning in life has been seen as crucial to well-being, also – and especially – in later life. This study focused on the social complexity of meaning making processes and the role of religion and spirituality in them, by finding out: 1) How are meaning-making practices connected with religion and spirituality for Finnish retirement migrants of the boomer generation? 2) What does the role of religion and spirituality in meaning-making practices teach us about the relation between individual and social aspects of meaning making? This was done by examining a particular group of older persons: Finnish retirement migrants aged 60 or over in Costa del Sol, Spain. The material for this study consists of 58 texts (written correspondence, dataset 1, year 2009), 10 semi-structured interviews (dataset 2, year 2011), and 30 completed online surveys with open ended questions (dataset 3, year 2019). Key findings are, that religion and spirituality are present in the lives of our informants in a variety of ways, playing a significant role in their meaning making, and that they appear as intertwined and not so easy to separate. A variety of religious and non-religious forms of spirituality exist in this population, and all of these forms can be relevant factors in meaning making. Also, the engagement in meaning making, contrary to what has been suggested in some of the literature about meaning in later life, does not only occur in response to confrontations with health issues, death or other major life events. Instead, we found that meaning making occurs as a process that is often inherent to daily activities which may seem ‘trivial’, but in fact turn out to be important sources of purpose, values and connectedness. Contrary to the dominant modern ideal of the authentic, self-sufficient human agent, which is based on a problematically atomistic and individualistic anthropology, (Taylor 1991), for our respondents their authentic subject position is embedded in the social practices of their daily lives, which nourish their individual spirituality and are vital to making meaning.